CIMAvax-EGF: A New Therapeutic Vaccine for Advanced Non-Small Cell Lung Cancer Patients - Saavedra, Danay; Crombet, Tania (Frontiers in Immunology, 2017)
Lung cancer is the common fatal illness with the highest incidence and mortality globally. Epidermal Growth Factor Receptor (EGFR) overexpression by tumor cells is associated with uncontrolled proliferation, angiogenesis, anti-apoptotic signals, metastization and invasiveness. Cimavax-EGF vaccine consists of a chemical conjugate of the EGF with the P64 protein derived from the Meningitis B bacteria and Montanide ISA 51, as adjuvant. The vaccine is projected to induce antibodies against EGF that results in EGF withdrawal. Cimavax-EGF demonstrated to be safe and immunogenic in advanced NSCLC patients. The efficacy study was an open-label, multicentric Phase III clinical trial, which enrolled 405 advanced NSCLC patients. Patients with proven stage IIIB/IV NSCLC, who had completed 4 to 6 cycles of chemotherapy were randomized to receive cimavax-EGF or best supportive care. Cimavax-EGF resulted in a significantly larger overall survival in patients receiving at least four doses. High EGF concentration at baseline was a good predictive biomarker of the vaccine activity and a poor prognostic biomarker for the non-treated population. The proportion of CD8+CD28- cells, CD4 cells and the CD4/CD8 ratio after first-line chemotherapy was also associated with cimavax-EGF clinical benefit. After completing the Phase III, a Phase IV trial was done where the vaccine was administered in primary care units. Administering the vaccine at primary care institutions granted better access and treatment compliance. Safety was confirmed. Several clinical trials are currently ongoing to validate EGF as a predictive biomarker of cimavax-EGF efficacy.